Molecular genetics of Kruppel, a gene required for segmentation of the Drosophila embryo. - Preiss, A.; Rosenberg, U.B.; Kienlin, A.; Seifert, E.; Jäckle, H. (Nature, 1985)
Krüppel is a member of the 'gap' class of segmentation genes of Drosophila melanogaster, mutations of which cause contiguous groups of segments of the fruitfly embryo to fail to develop. In the case of Krüppel mutant embryos, thoracic and anterior abdominal segments are deleted. The molecular cloning of the Krüppel locus will lead to an understanding of the crucial role that gap genes seem to have in early embryonic development. It has already allowed the identification of a blastoderm-specific Krüppel transcript and the phenotypic rescue of mutant embryos by injected cloned DNA.